Investigating the Impact of Estrogen Levels on Voiding Characteristics, Bladder Structure, and Related Proteins in a Mouse Model of Menopause-Induced Lower Urinary Tract Symptoms - Chenglong Zhang; Yuangui Chen; Lingxuan Yin; Guoxian Deng; Xiaowen Xia; Xiaoshuang Tang; Yifeng Zhang; Junan Yan (Biomolecules)
Lower urinary tract symptoms (LUTS) are common in postmenopausal women. These symptoms are often linked to decreased estrogen levels following menopause. This study investigated the relationship between estrogen levels, alterations in bladder tissue structure, bladder function, and the incidence of urinary frequency. An age-appropriate bilateral ovariectomized mouse model (OVX) was developed to simulate conditions of estrogen deficiency. Mice were divided into three groups: a sham-operated control group, OVX, and an estradiol-treated group. The assessments included estrogen level measurement, urination frequency, cystometry, histological analysis, immunofluorescence staining, and real-time quantitative PCR. Additionally, we quantified the expression of the mechanosensitive channel proteins Piezo1 and TRPV4 in mouse bladder tissues. Lower estrogen levels were linked to increased voiding episodes and structural changes in mouse bladder tissues, notably a significant increase in Collagen III fiber deposition. There was a detectable negative relationship between estrogen levels and the expression of Piezo1 and TRPV4, mechanosensitive proteins in mouse bladder tissues, which may influence voiding frequency and nocturia. Estrogen treatment could improve bladder function, decrease urination frequency, and reduce collagen deposition in the bladder tissues. This study explored the connection between estrogen levels and urinary frequency, potentially setting the stage for novel methods to address frequent urination symptoms in postmenopausal women.